From Posts to Protection: Understanding User-Generated Safety Content on Reddit - Almoqbel, Mashael Yousef (International Journal of Computational and Experimental Science and Engineering, 2025)
This study investigates discussions surrounding safety on Reddit to understand the topics and user comments related to safety concerns. By employing content analysis, the research explores the themes that emerge in posts and responses within safety-focused subreddits. The findings are interpreted through the lenses of Social Support Theory and Uses and Gratifications Theory, providing insight into how individuals seek information, express concerns, and interact with others about safety-related issues. The analysis reveals key themes such as personal safety, community vigilance, and the sharing of safety resources. Based on the findings, several design implications are suggested to improve the user experience and effectiveness of safety-related content on social platforms. These implications aim to enhance community engagement, foster supportive interactions, and better address user needs in digital spaces.